International prospective observational study on intracranial pressure in intensive care (ICU): the SYNAPSE-ICU study protocol. Issue 4 (20th April 2019) - Citerio, Giuseppe; Prisco, Lara; Oddo, Mauro; Meyfroidt, Geert; Helbok, Raimund; Stocchetti, Nino; Taccone, Fabio; Vincent, Jean-Louis; Robba, Chiara; Elli, Francesca; Sala, Elisa; Vargiolu, Alessia; et al.
Abstract : Introduction: Intracranial pressure (ICP) monitoring is commonly used in neurocritical care patients with acute brain injury (ABI). Practice about indications and use of ICP monitoring in patients with ABI remains, however, highly variable in high-income countries, while data on ICP monitoring in low and middle-income countries are scarce or inconsistent. The aim of the SYNAPSE-ICU study is to describe current practices of ICP monitoring using a worldwide sample and to quantify practice variations in ICP monitoring and management in neurocritical care ABI patients. Methods and analysis: The SYNAPSE-ICU study is a large international, prospective, observational cohort study. From March 2018 to March 2019, all patients fulfilling the following inclusion criteria will be recruited: age >18 years; diagnosis of ABI due to primary haemorrhagic stroke (subarachnoid haemorrhage or intracranial haemorrhage) or traumatic brain injury; Glasgow Coma Score (GCS) with no eye opening (Eyes response=1) and Motor score ≤5 (not following commands) at ICU admission, or neuro-worsening within the first 48 hours with no eye opening and a Motor score decreased to ≤5. Data related to clinical examination (GCS, pupil size and reactivity, Richmond Agitation-Sedation Scale score, neuroimaging) and to ICP interventions (Therapy Intensity Levels) will be recorded on admission, and at day 1, 3 and 7. The Glasgow Outcome Scale Extended (GOSE) will be collected at discharge from ICU and from hospital and at 6-month follow-up. The impact of ICP monitoring and ICP-driven therapy on GOSE will be analysed at both patient and ICU level. Ethics and dissemination: The study has been approved by the Ethics Committee 'Brianza' at the Azienda Socio Sanitaria Territoriale (ASST)-Monza (approval date: 21 November 2017). Each National Coordinator will notify the relevant ethics committee, in compliance with the local legislation and rules. Data will be made available to the scientific community by means of abstracts submitted to the European Society of Intensive Care Medicine annual conference and by scientific reports and original articles submitted to peer-reviewed journals. Trial registration number: NCT03257904 .